Advanced theory of peat vehicle mobility - Rahman, Mohammed Ataur; Afroz, Rafia (VDM Verleg, 2011)
The Advanced Theory of Peat vehicle has been written with emphasizing the fundamental engineering principles underlying the determination of the mechanical properties of peat terrain, developing simulation models for optimizing the vehicle design parameters, the rational design and development non guided vehicle more accurately in order to control the vehicle during traversing on unprepared peat terrain both in straight and turning motion. This book is intended to introduce senior undergraduate and beginning of the postgraduate students to study on the theory of tracked vehicle and peat terrain mechanical properties determination. An analytical framework for determining the mechanical properties of peat in view of predicting the tractive performance of vehicle is presented. It takes into account the loadsinkage and shearing characteristics of peat. The measuring techniques of the stiffness of peat’s surface mat and underlying weak peat are also presented. Vehicle basic design parameters analysis, including the track width, ground contact length, pitch and grouser height, idler diameter and location, sprocket diameter and location, road-wheel diameter and geometrical arrangement, the ratio of the road-wheel spacing to track pitch, location of the center of gravity (CG) and optimization the vehicle design parameters are discussed. An innovative instrumentation system is presented in this book to prevent the vehicle from sinking and investigate the vehicle performance. The performance investigation of the vehicle both in straight and turning motion are discussed in theoretically and experimentally. The most effective statistical tool is show the significance difference of the vehicle performance from one peat terrain to other.